The Effect of Non-cash Transactions on The Money Supply Indonesia (2009:Q1 – 2019:Q2) - Eka Ulina; Rogatianus Maryatmo (Conference Series, 2020)
This study explores and investigates the impacts of the volume of non-cash transactions through automated teller machine cards (atm), credit cards, and electronic money to money supply in Indonesia from 2009 quarter one to 2019 quarter two. This study uses secondary data obtained from Bank Indonesia. The analysis tool uses multiple linear regression. Secondary data used is quarterly data on money supply and the volume of transactions of atm debit cards, credit cards, and electronic transactions. The results showed that the volume of credit card and electronic money transactions positively and significantly determine the money supply. The money supply is more elastic in response to the change in the volume of the credit card transaction.